The Importance of Surface Adsorbates in Solution-Processed Thermoelectric Materials: The Case of Snse - Liu, Yu; Genç, Aziz; Calcabrini, Mariano; Yu, Yuan; Genç, Aziz; Chang, Cheng; Costanzo, Tommaso; Kleinhanns, Tobias (Wiley, 2021)
Solution synthesis of particles emerges as an alternative to prepare thermoelectric materials with less demanding processing conditions than conventional solid-state synthetic methods. However, solution synthesis generally involves the presence of additional molecules or ions belonging to the precursors or added to enable solubility and/or regulate nucleation and growth. These molecules or ions can end up in the particles as surface adsorbates and interfere in the material properties. This work demonstrates that ionic adsorbates, in particular Na+ ions, are electrostatically adsorbed in SnSe particles synthesized in water and play a crucial role not only in directing the material nano/microstructure but also in determining the transport properties of the consolidated material. In dense pellets prepared by sintering SnSe particles, Na remains within the crystal lattice as dopant, in dislocations, precipitates, and forming grain boundary complexions. These results highlight the importance of considering all the possible unintentional impurities to establish proper structure-property relationships and control material properties in solution-processed thermoelectric materials.
Keywords: Grain boundaries; Liquid sintering; solution processing; Surface chemistry; Thermoelectricity